Preparation method and application of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material
By loading carbon dots and carbon black composite materials on basalt fiber fabrics, combining water storage tanks and heat insulation layers, a carbon dot/carbon black solar interface evaporation device is constructed, which solves the problems of heat concentration and high energy consumption in seawater desalination technology. It achieves efficient freshwater production and salt resistance.
Patent Information
- Application Number
- CN202411323384.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Existing seawater desalination technologies such as membrane distillation and mechanical steam recompression have problems such as high investment costs and large energy consumption. It is difficult for carbon-based materials to effectively concentrate the heat generated by solar radiation in solar interface evaporation technology, which affects the evaporation efficiency.
Using basalt fiber fabric as the substrate, the carbon dot and carbon black composite material is loaded through impregnation coating technology, combined with the water storage tank and heat insulation layer, a carbon dot/carbon black solar interface evaporation device is constructed to enhance the hydrophilicity and photothermality of the material. Performance, improve seawater evaporation efficiency.
In a high-concentration seawater environment, a large amount of freshwater production is achieved, providing an economical and environmentally friendly freshwater resource solution, and showing a high evaporation rate and good salt resistance in simulated seawater evaporation performance tests.
Smart Images

Figure CN119194845A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbon nanomaterials, and in particular to a preparation method and application of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material. Background Art
[0002] Freshwater shortage has become a global problem. Desalination of seawater is one of the effective ways to alleviate the shortage of freshwater resources. Traditional seawater desalination technologies such as membrane distillation and mechanical vapor recompression have a series of problems such as high investment cost and high energy consumption. Solar energy is a green and clean energy. It is necessary and practical to improve the utilization efficiency of solar energy resources. Solar interface evaporation technology uses solar energy as the only energy input, uses an evaporator to concentrate heat at the gas-liquid interface, and obtains fresh water through evaporation. This technology is green and environmentally friendly and highly sustainable.
[0003] Evaporator materials are the core of solar interfacial evaporation technology. Currently, commonly used materials include carbon-based materials, semiconductor materials, plasma metal nanoparticles and polymers. Compared with semiconductors and plasma materials, carbon-based materials can widely absorb almost all wavelengths of sunlight in the solar spectrum, and are low-cost and more environmentally friendly. Common carbon-based materials include carbon black, carbon nanotubes, graphene, porous carbon, etc. Although these carbon-based materials have many advantages, such as light weight, non-toxicity, stable performance, etc., these materials themselves have high thermal conductivity, which is not conducive to concentrating the heat generated by solar radiation on the surface of the photothermal material.
[0004] In contrast, carbon dots have an ideal heat-insulating quasi-spherical structure, and the surface of carbon dots contains oxygen-containing functional groups such as hydroxyl and carboxyl, which can form hydrogen bonds with water molecules to reduce the evaporation enthalpy. As reported in patent CN109399606A, carbon dots are loaded onto foam to achieve high photothermal conversion of foam, but no evaporation performance test of simulated seawater is conducted. As reported in patent CN113968599A, carbon dots are added to the sponge to reduce heat loss, but no evaporation performance test of simulated seawater is conducted. It can be seen that when carbon dots are combined with some photothermal materials in practical applications, they can not only enhance the material's ability to absorb sunlight, but also gather heat to a specific location. Therefore, the present invention integrates the hydrophilicity, thermal insulation performance of carbon dots and the photothermal conversion performance of carbon black, takes basalt fiber fabric as the substrate, combines the impregnation coating technology, and prepares photothermal fabrics with excellent photothermal conversion performance, and then further combines the water storage tank and the thermal insulation layer and other structures to finally construct a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device, and conducts a simulated seawater evaporation performance test. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies in the prior art and provide a method for preparing and applying a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material. The carbon dot / carbon black composite material is loaded onto the fabric by impregnation coating, which not only improves the hydrophilicity of the basalt fiber fabric, but also improves its photothermal performance. The method of the present invention has a simple process, is easy to mass produce, and can still produce a large amount of fresh water in a high-concentration seawater environment, providing an effective solution to the shortage of fresh water resources.
[0006] The method for preparing a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material of the present invention comprises first preparing carbon dots, then combining the carbon dots with carbon black by hydrothermal reaction, and then loading the carbon dot / carbon black composite material onto the fabric by a dipping coating method. The specific operation is performed according to the following steps:
[0007] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 50-150 mesh screen to obtain leaf powder;
[0008] b. Preparation of carbon dots by hydrothermal method: the leaf powder obtained in step a is mixed with ultrapure water at a mass ratio of 1:30-60, ultrasonically dispersed for 10-50 min, and then transferred to a reactor lined with polytetrafluoroethylene, sealed and placed in an electric constant temperature blast drying oven, reacted at a temperature of 180-220°C for 6-12 h, and after the reaction, the reactor was naturally cooled to room temperature to obtain a brown liquid;
[0009] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 10-20 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 24-72 h using a 500-3000 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0010] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0011] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d is mixed with 100 mL of ultrapure water at a mass ratio of 1:5-30, ultrasonically dispersed for 1-5 min, and then 3 wt % of carbon black is added, ultrasonically dispersed for 5-10 min while stirring, and then transferred to a reactor lined with polytetrafluoroethylene, sealed and placed in an electric constant temperature blast drying oven at a temperature of 180° C. for reaction for 3 h. After the reaction is completed, the reactor is naturally cooled to room temperature, the liquid in the reactor is filtered by suction, and then the black powder on the filter paper is placed in an electric constant temperature blast drying oven, dried at a temperature of 40-80° C. for 4-8 h, and the obtained product is collected for standby use;
[0012] f. Pretreatment of basalt fiber fabric: wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 1-3 mol L -1 In sodium hydroxide solution, after sealing, heat treat at 80-100℃ for 2-4h, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0013] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: first, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%, and then ultrasonic dispersion treatment is performed for 0.5-1.5h using an ultrasonic cell disruptor with a power of 250W, and then the front and back sides of the basalt fiber fabric pretreated in step f are respectively immersed in the solution and allowed to stand for 1-3min, and then the fabric is taken out and dried in an oven at a temperature of 80-90°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a concentration of 0.1-0.5mol L -1 The fabric is immersed in a calcium chloride solution for cross-linking for 8-12 hours, and finally the excess calcium chloride on the surface of the fabric is washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0014] The basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained by the method is used in the preparation of seawater desalination. The device involved is composed of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1), a water storage tank (2), a heat insulation layer (3), a condenser (4), a collector (5) and sunlight (6). The heat insulation layer (3) is provided at the upper end of the water storage tank (2). The heat insulation layer (3) is made of polystyrene foam and is used for heat insulation. The two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) are inserted into the water storage tank (2). The collector (5) is provided at the bottom of the water storage tank (2). The condenser (4) is arranged in the collector (5). The specific operation is carried out according to the following steps:
[0015] The two ends of the obtained basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) are inserted into a water storage tank (2) to transport seawater moisture through capillary action. The basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) containing seawater moisture is then heated by capturing sunlight (6) to generate water vapor. The water vapor is liquefied into liquid fresh water through a condenser (4), flows downward along the inner wall of the condenser (4) to a collector (5), and the fresh water is enriched in the collector (5).
[0016] The present invention discloses a method for preparing and applying a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material. The carbon dot is prepared from leaves, and then the carbon dot and carbon black are combined by hydrothermal reaction. The carbon dot / carbon black composite material is then loaded onto the basalt fiber fabric by an impregnation coating method to obtain the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material. Then, the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material is combined with a water storage tank and a heat insulation layer and other structures to finally construct the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device. The carbon dot / carbon black composite material not only improves the hydrophilicity of the basalt fiber fabric, but also improves its photothermal performance. The technical solution adopted by the present invention is not only simple in process and easy to mass produce, but also can still produce a large amount of fresh water in a high-concentration seawater environment, providing an effective solution to the shortage of freshwater resources, and has broad application prospects in the field of seawater desalination.
[0017] The advantages of the present invention compared to the prior art are:
[0018] (1) The present invention uses leaves to prepare carbon dots, which is green, economical, and environmentally friendly. The leaves themselves have oxygen-containing functional groups such as hydroxyl and carboxyl groups, which can also improve the hydrophilicity of the material.
[0019] (2) The carbon dot / carbon black composite material prepared by the present invention has good heat absorption performance, which is beneficial to the conversion of sunlight. Its nanostructure improves the specific surface area of basalt fiber fabric and increases the evaporation area.
[0020] (3) The present invention uses fabric as the substrate to prepare the photothermal layer. Its good porosity is conducive to the efficient transportation of water. Its lightness and flexibility not only facilitate folding and transportation, but also can be cut and shaped as needed, making it suitable for different application scenarios. By simply impregnating the fabric with the loaded photothermal material, not only can the photothermal performance of the material be enhanced, but it can also be mass-produced.
[0021] (4) Under one sunlight intensity, the evaporation rate of pure water by the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device constructed by the present invention is 2.05 kg m -2 h -1 , the evaporation rate of simulated seawater is 1.88 kg m -2 h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The transmission electron microscope morphology, particle size distribution and high-resolution transmission electron microscope images of the carbon dots prepared in the present invention, wherein (a) is a transmission electron microscope morphology image, (b) is a particle size distribution image, and (c) is a high-resolution transmission electron microscope morphology image (the inset is the lattice spacing of the carbon dots);
[0023] Figure 2 The scanning electron microscope morphology images of carbon dots, original fabrics, carbon dot-loaded fabrics, carbon black-loaded fabrics, and basalt fiber fabric-loaded carbon dot / carbon black photothermal fabrics prepared by the present invention, wherein (a) is carbon dots, (b) is original fabrics, (c) is carbon dot-loaded fabrics, (d) is carbon black-loaded fabrics, and (e) is basalt fiber fabric-loaded carbon dot / carbon black photothermal fabrics;
[0024] Figure 3 A diagram of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device constructed in the present invention, wherein (1) is a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material, (2) is a water storage tank, (3) is a heat insulation layer, (4) is a condenser, (5) is a collector, and (6) is sunlight;
[0025] Figure 4 The evaporation performance test of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material prepared by the present invention is to test the change of pure water mass loss of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material with different carbon dot to carbon black ratios under one sunlight intensity;
[0026] Figure 5 The salt resistance test of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material prepared by the present invention is to test the change of the simulated seawater mass loss of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material under one sunlight intensity;
[0027] Figure 6 The changes in the concentrations of four ions in the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device constructed by the present invention before and after treating simulated seawater. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments, and the exemplary description is used to help those skilled in the art further understand the present invention. However, the following are only preferred embodiments of the present invention, and cannot be understood as limiting the technical solution provided by the present invention, nor can they limit the scope of the patent of the present invention. Any non-substantial changes that do not deviate from the concept of the present invention are also included in the scope of patent protection of the present invention.
[0029] Example 1
[0030] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 50-mesh sieve to obtain leaf powder;
[0031] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:60, and ultrasonically dispersed for 50 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven for reaction at 180°C for 6 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0032] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 20 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 24 h using a 3000 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0033] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0034] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:5, and ultrasonically dispersed for 1 min. Then, 3 wt% of carbon black was added, and ultrasonically dispersed for 5 min while stirring. Then, the mixture was transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven at a temperature of 180°C for reaction for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction. Then, the black powder on the filter paper was placed in an electric constant temperature blast drying oven, and dried at a temperature of 40°C for 8 h. The obtained product was collected for later use;
[0035] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 1 mol L -1 After sealing, heat-treat at 80℃ for 2h in sodium hydroxide solution, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0036] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 0.5h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 1min. Then, the fabric is taken out and dried in an oven at a temperature of 80°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.1mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 8 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0037] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 1.5 kg m -2 h -1 .
[0038] Example 2
[0039] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 70-mesh sieve to obtain leaf powder;
[0040] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:50, and ultrasonically dispersed for 40 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven for reaction at 220°C for 8 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0041] c. Carbon dot purification: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 10 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 36 h using a 500 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0042] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0043] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:5, and ultrasonically dispersed for 2 min, then 3 wt% of carbon black was added, and ultrasonically dispersed for 10 min while stirring, and then transferred to a reactor lined with polytetrafluoroethylene, sealed and placed in an electric constant temperature blast drying oven at a temperature of 180°C for reaction for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction, and then the black powder on the filter paper was placed in an electric constant temperature blast drying oven, dried at a temperature of 50°C for 5 h, and the obtained product was collected for standby use;
[0044] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 2 mol L -1 In sodium hydroxide solution, after sealing, heat-treat at 90°C for 3h, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60°C for 1h;
[0045] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 1h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 2min. Then, the fabric is taken out and dried in an oven at a temperature of 85°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.2mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 9 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0046] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 1.52 kg m -2 h -1 .
[0047] Example 3
[0048] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 100-mesh sieve to obtain leaf powder;
[0049] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:30, and ultrasonically dispersed for 25 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven. The reaction was carried out at a temperature of 180°C for 12 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0050] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 20 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water using a 1000 Da dialysis membrane for 48 h, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0051] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0052] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:25, and ultrasonically dispersed for 5 min. Then, 3 wt % of carbon black was added, and ultrasonically dispersed for 8 min while stirring. Then, the mixture was transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven at a temperature of 180° C. for reaction for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction. Then, the black powder on the filter paper was placed in an electric constant temperature blast drying oven, and dried at a temperature of 60° C. for 5 h. The obtained product was collected for later use.
[0053] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 3 mol L -1After sealing, heat-treat at 100℃ for 3h in sodium hydroxide solution, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0054] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 1.5h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 3min. Then, the fabric is taken out and dried in an oven at a temperature of 85°C, so that the carbon dot / carbon black composite material can grow in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.2mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 10 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0055] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 1.71 kg m -2 h -1 .
[0056] Example 4
[0057] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 120-mesh sieve to obtain leaf powder;
[0058] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:40, and ultrasonically dispersed for 50 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven. The reaction was carried out at a temperature of 220°C for 10 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0059] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 10 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 72 h using a 2000 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0060] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0061] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:30, and ultrasonically dispersed for 1 min. Then, 3 wt% of carbon black was added, and ultrasonically dispersed for 10 min while stirring. Then, the mixture was transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven at a temperature of 180° C. to react for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction. Then, the black powder on the filter paper was placed in an electric constant temperature blast drying oven, and dried at a temperature of 80° C. for 8 h. The obtained product was collected for later use;
[0062] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 3 mol L -1 After sealing, heat-treat at 100℃ for 2h in sodium hydroxide solution, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0063] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 1h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 3min. Then, the fabric is taken out and dried in an oven at a temperature of 90°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.5mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 12 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0064] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 2.05 kg m -2 h -1 .
[0065] Example 5
[0066] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 150-mesh sieve to obtain leaf powder;
[0067] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:50, and ultrasonically dispersed for 45 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven for reaction at 220°C for 8 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0068] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 18 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 24 h using a 1500 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0069] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0070] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:25, and ultrasonically dispersed for 4 min. Then, 3 wt% of carbon black was added, and ultrasonically dispersed for 6 min while stirring. Then, the mixture was transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven at a temperature of 180° C. for reaction for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction. Then, the black powder on the filter paper was placed in an electric constant temperature blast drying oven, and dried at a temperature of 60° C. for 5 h. The obtained product was collected for later use;
[0071] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 2 mol L -1After sealing, heat-treat at 100℃ for 4h in sodium hydroxide solution, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0072] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 1.5h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 2min. Then, the fabric is taken out and dried in an oven at a temperature of 85°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.4mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 9 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0073] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 1.67 kg m -2 h -1 .
[0074] Example 6
[0075] a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 150-mesh sieve to obtain leaf powder;
[0076] b. Preparation of carbon dots by hydrothermal method: The leaf powder obtained in step a was mixed with ultrapure water at a mass ratio of 1:45, and ultrasonically dispersed for 35 min. The mixture was then transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven for reaction at 200°C for 6 h. After the reaction was completed, the reactor was naturally cooled to room temperature to obtain a brown liquid.
[0077] c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 20 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 72 h using a 3000 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution;
[0078] d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder;
[0079] e. Preparation of carbon dot / carbon black composite material: The carbon dot powder obtained in step d was mixed with 100 mL of ultrapure water at a mass ratio of 1:30, and ultrasonically dispersed for 5 min. Then, 3 wt % of carbon black was added, and ultrasonically dispersed for 10 min while stirring. Then, the mixture was transferred to a reactor lined with polytetrafluoroethylene, sealed, and placed in an electric constant temperature blast drying oven at a temperature of 180° C. to react for 3 h. After the reaction was completed, the reactor was naturally cooled to room temperature, and the liquid in the reactor was filtered by suction. Then, the black powder on the filter paper was placed in an electric constant temperature blast drying oven, and dried at a temperature of 80° C. for 8 h. The obtained product was collected for later use.
[0080] f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 3 mol L -1 After sealing, heat-treat at 100℃ for 4h in sodium hydroxide solution, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1h;
[0081] g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: First, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3wt%. Then, an ultrasonic cell disruptor with a power of 250W is used for ultrasonic dispersion treatment for 1.5h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 3min. Then, the fabric is taken out and dried in an oven at a temperature of 90°C, so that the carbon dot / carbon black composite material can be grown in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.5mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 12 hours, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material;
[0082] h. Construction of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device: insert the two ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained in step g into the water storage tank to transport water through capillary action, and the middle part captures sunlight to heat the water at the gas-liquid interface to generate water vapor; the insulation layer is made of polystyrene foam and is located above the water storage tank for heat insulation. The evaporation rate of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device is 1.57 kg m -2 h -1 .
[0083] Example 7
[0084] The application of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained by the method described in Example 4 in the preparation of seawater desalination, wherein the device involved is composed of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material 1, a water storage tank 2, an insulation layer 3, a condenser 4, a collector 5 and sunlight 6, an insulation layer 3 is provided at the upper end of the water storage tank 2, and the insulation layer 3 is made of polystyrene foam for heat insulation; both ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material 1 are inserted into the water storage tank 2, a collector 5 is provided at the bottom of the water storage tank 2, and the condenser 4 is arranged in the collector 5, and the specific operation is carried out according to the following steps:
[0085] The two ends of the obtained basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material 1 are inserted into a water storage tank 2 to transport seawater moisture through capillary action. The basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material 1 containing seawater moisture is then heated by capturing sunlight 6 to generate water vapor. The water vapor is liquefied into liquid fresh water through a condenser 4 and flows downward along the inner wall of the condenser 4 to a collector 5, where fresh water is enriched.
[0086] The constructed basalt fiber fabric-based carbon dot / carbon black solar interface evaporation device was used to desalinate a high-salinity simulated seawater sample prepared using the ASTM D1141-2021 standard method under one sun intensity. The mass loss of the simulated seawater is shown in the figure below. Figure 5 , the evaporation rate is 1.88 kg m -2 h -1 ; The Na content of simulated seawater before and after treatment was determined by inductively coupled plasma emission spectroscopy + Mg 2+ , K + , Ca 2+ The concentration changes are as follows Figure 6 After treatment, the concentrations of four ions in the water samples were reduced by four orders of magnitude, far exceeding the "Guidelines for Drinking Water Quality" formulated by the World Health Organization.
Claims
1. A method for preparing basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material, characterized in that: First, carbon dots are prepared, then the carbon dots are combined with carbon black by hydrothermal reaction, and then the carbon dots / carbon black composite material is loaded onto the fabric by dip coating. The specific operation is carried out in the following steps: a. Leaf pretreatment: clean and dry the leaves, then crush them with a grinder, and sieve them with a 50-150 mesh screen to obtain leaf powder; b. Preparation of carbon dots by hydrothermal method: the leaf powder obtained in step a is mixed with ultrapure water at a mass ratio of 1:30-60, and ultrasonically dispersed for 10-50 min, and then transferred to a reactor lined with polytetrafluoroethylene, sealed and placed in an electric constant temperature blast drying oven, reacted at a temperature of 180-220°C for 6-12 h, and after the reaction, the reactor was naturally cooled to room temperature to obtain a brown liquid; c. Purification of carbon dots: The brown liquid obtained in step b was centrifuged at 10,000 rpm for 10-20 min to separate impurities and large particles, and then the supernatant containing carbon dots was dialyzed with ultrapure water for 24-72 h using a 500-3000 Da dialysis membrane, and then the dialyzate was filtered using a 0.2 μm water filter membrane to obtain a carbon dot solution; d. Carbon dot extraction: freeze-dry the purified carbon dot solution in step c in a freeze dryer at -40°C to obtain carbon dot powder; e. Preparation of carbon dot / carbon black composite material: the carbon dot powder obtained in step d is mixed with 100 mL ultrapure water at a mass ratio of 1:5-30, ultrasonically dispersed for 1-5 min, then 3 wt% of carbon black is added, ultrasonically dispersed for 5-10 min while stirring, and then transferred to a reactor lined with polytetrafluoroethylene, sealed and placed in an electric constant temperature blast drying oven at a temperature of 180 ° C for reaction for 3 hours, and after the reaction is completed, the reactor is naturally cooled to room temperature, the liquid in the reactor is filtered by suction, and then the black powder on the filter paper is placed in an electric constant temperature blast drying oven, dried at a temperature of 40-80 ° C for 4-8 hours, and the obtained product is collected for use; f. Pretreatment of basalt fiber fabric: Wash the basalt fiber fabric with ultrapure water and anhydrous ethanol in turn, dry it naturally, and then soak the middle part of the fabric in 1-3 mol L -1 In sodium hydroxide solution, after sealing, heat treat at 80-100℃ for 2-4 h, take out the fabric, wash the surface of the fabric with ultrapure water until the cleaning solution is neutral, put the washed fabric into an electric constant temperature blast drying oven, and dry it at 60℃ for 1 h; g. Preparation of basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material: first, hexadecyltrimethylammonium bromide, sodium alginate and the carbon dot / carbon black composite material obtained in step e are mixed in a mass ratio of 3:3:1, and a certain mass of deionized water is added to prepare a solution so that the mass concentration of carbon dot / carbon black is 0.3 wt%. Then, an ultrasonic cell disruptor with a power of 250 W is used for ultrasonic dispersion treatment for 0.5-1.5 h. Then, the front and back sides of the basalt fiber fabric pretreated in step f are immersed in the solution respectively, and the solution is allowed to stand for 1-3 min. Then, the fabric is taken out and dried in an oven at a temperature of 80-90 °C, so that the carbon dot / carbon black composite material can grow in situ on the basalt fiber fabric. This process is repeated 5 times, and then the fabric is placed in a 0.1-0.5 mol L -1 The fabric was immersed in a calcium chloride solution for cross-linking for 8-12 h, and finally the excess calcium chloride on the surface of the fabric was washed off and dried in an oven to obtain a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material.
2. An application of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material obtained by the method as claimed in claim 1 in the preparation of seawater desalination, wherein the device involved is composed of a basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1), a water storage tank (2), a heat insulation layer (3), a condenser (4), a collector (5) and sunlight (6), wherein a heat insulation layer (3) is provided at the upper end of the water storage tank (2), and the heat insulation layer (3) is made of polystyrene foam for heat insulation; both ends of the basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) are inserted into the water storage tank (2), a collector (5) is provided at the bottom of the water storage tank (2), and the condenser (4) is provided in the collector (5), and the specific operation is carried out according to the following steps: The two ends of the obtained basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) are inserted into a water storage tank (2) to transport seawater moisture through capillary action. The basalt fiber fabric-based carbon dot / carbon black solar interface evaporation material (1) containing seawater moisture is then heated by capturing sunlight (6) to generate water vapor. The water vapor is liquefied into liquid fresh water through a condenser (4), flows downward along the inner wall of the condenser (4) to a collector (5), and the fresh water is enriched in the collector (5).
Citation Information
Cited By
Silver-copper bimetal electric heating layer coupling solar interface evaporation system and preparation method and application of silver-copper bimetal electric heating layer coupling solar interface evaporation system
CN121342130A
